1997
DOI: 10.1006/qres.1997.1919
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatic Reconstruction of April–May Temperature Fluctuations in the Western Himalaya of India Since A.D. 1698

Abstract: Ring-width chronologies of Himalayan cedar (Cedrus deodara (D. Don.) G. Don.), Himalayan pine (Pinus wallichiana A. B. Jackson), and Himalayan spruce (Picea smithiana (Wall.) Boiss.) from the western Himalayan region, India, have been used to reconstruct mean April–May temperature back to A. D. 1698. The reconstruction correlates significantly with the average April–May instrumental temperature record (r= +0.62, 1876–1988) and is characterized by annual to multiyear fluctuations. The most striking feature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 11 publications
4
27
0
Order By: Relevance
“…Although the statistics for each model did not differ much from each other, the best results were obtained using combination of species. This result confirmed the idea and validity of using multispecies models previously proposed by Yadav et al (1997) or Garcıá-Suárez et al (2009).…”
Section: Assessment Of Potential For Climate Reconstructionsupporting
confidence: 89%
“…Although the statistics for each model did not differ much from each other, the best results were obtained using combination of species. This result confirmed the idea and validity of using multispecies models previously proposed by Yadav et al (1997) or Garcıá-Suárez et al (2009).…”
Section: Assessment Of Potential For Climate Reconstructionsupporting
confidence: 89%
“…Correlation analysis indicated that spring (April) temperature also has biological relevance for interannual variations in tree growth at the high elevation sites, and similar results have been reported for the Western Himalayas of India and Nepal (Yadav et al 1997, Cook et al 2003. The positive influence of spring temperature on tree growth is evident, as high spring temperatures lead to the breaking of dormancy and the resumption of physiological activity in the tree, thus increasing the duration of the current growing season (Lebourgeois et al 2005).…”
Section: The Association Of Tree Growth With Climatesupporting
confidence: 76%
“…These negative climatic effects may limit cambial activity by affecting the photosynthetic rate and, hence, the possibility of radial expansion (DeLucia & Smith 1987). The climatic variable most strongly correlated to radial growth is also summer temperature for the east and northeast Tibetan Plateau (Bräuning 2006), the source region of the Yangtze River (Liang et al 2008), the central Hengduan Mountains (Fan et al 2009a, Li et al 2011a, and the Western Sichuan Plateau (Shao & Fan 1999, Li et al 2010, 2011b.Correlation analysis indicated that spring (April) temperature also has biological relevance for interannual variations in tree growth at the high elevation sites, and similar results have been reported for the Western Himalayas of India and Nepal (Yadav et al 1997, Cook et al 2003. The positive influence of spring temperature on tree growth is evident, as high There is strong circumstantial evidence that winter temperatures play a major role in modulating mean climate-tree growth relationships.…”
mentioning
confidence: 55%
“…Negative influences of early summer warmth on tree growth were reported for S. przewalskii on the northeastern TP (Gou et al 2008;Liang et al 2010;Liu et al 2006;Shao et al 2010;Sheppard et al 2004;Zhang et al 2003). In the western Himalayas, warm summers also limit the growth of Juniperus polycarpos (Yadav et al 2010), Cedrus deodara (Yadav et al 1997(Yadav et al , 1999Yadav et al 2004) and Abies pindrow (Hughes 1992). In addition, Cai et al (2008) found the limiting effect of May-Jun temperature on tree growth of Pinus tabulaeformis from the southeastern Chinese Loess Plateau.…”
Section: Resultsmentioning
confidence: 99%